ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS TENAGA KERJA TERHADAP HASIL PRODUKSI KECAP DI PABRIK KECAP SEGI TIGA - Ivan Susanto, Hendri; Milana, Lia (Universitas Majalengka, 2019)
The SEGI TIGA soy sauce factory is a factory engaged in the industry that produces soy sauce. In carrying out its production, it is very important to produce production. Labor is a major factor or driving force in producing and improving the quality of the workforce. The workforce will be more productive if the factors that increase productivity Labor support. The process of this research is preceded by the process of interviewing, observation, documentation followed by data collection where data collection uses the method of distributing questionnaires. From the results of processing questionnaire data, the factors that influence labor productivity on production yields, the most dominant factor influencing labor productivity in the triangular soy sauce factory is in terms of raw materials because when raw materials are available or easily obtained, work productivity will not disrupted or good, and market demand in the triangle ketchup factory using the Make To Order system (MTO) so the factory produces according to market demand.